The Original Ending of Mark : a New Case for the Authenticity of Mark 16:9-20 - Lunn, Nicholas P. (Cambridge : James Clarke & Co., 2015)
Although traditionally accepted by the church through the centuries, the longer ending of Mark's Gospel (16:9-20) has been relegated by modern scholarship to the status of a later appendage. The arguments for such a view are chiefly based upon the witness of the two earliest complete manuscripts of Mark, and upon matters of language and style. This work shows that these primary grounds of argumentation are inadequate. It demonstrates that the church fathers knew the Markan ending from the very earliest days, well over two centuries before the earliest extant manuscripts. The quantity of unique.
Front cover; Half title; Title page; Copyright; Contents; Preface; Acknowledgements; Abbreviations; 1. Introduction; 2. External Evidence (1): Biblical Manuscripts; 3. External Evidence (2): Patristic Citations; 4. Linguistic Evidence (1): Vocabulary and Style; 5. Linguistic Evidence (2): Other Features; 6. Literary Evidence; 7. Thematic Evidence; 8. The Longer Ending and the Gospels: The Question of Dependence; 9. Miscellaneous Issues; 10. The Cause of the Problem; 11. Summary and Conclusion; Bibliography; Back cover.
Includes bibliographical references.
Vendor-supplied metadata.
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, Textual; Bible; Bible; Bible. Mark -- Criticism, interpretation, etc; Bible. New Testament -- Criticism, Textual; Bible. New Testament -- Manuscipts, Greek; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; RELIGION / Biblical Criticism & Interpretation / New Testament; Electronic books; Criticism, interpretation, etc